Toward Innovative Governance: Developing Policy Instrument for an Effective Management of Nursing Home in Java, Indonesia - Asmorowati, Sulikah; Supeno, Eko; Schubert, Violeta; Nurfillaili, Izzatin Mukhlishoh; Nasution, Parlaungan Iffah; Nikmah, Syarifah (Universitas Negeri Surabaya, 2024)
Elderly people are those who have reached the age of sixty years and above. Based on data from the Central Statistics Agency (BPS) in 2021, the number of elderly in Indonesia is 29.3 million, which makes up to 10.82 percent of the total population. This number will continue to increase, leading to one of the world's most emerging problems, namely aging society. The issue of elderly people is an issue that must be paid attention to. Facts show that many elderly still have to work to meet their living needs. The increasing need for formal elder care provisions puts intensive pressure on providing elderly services and paying attention to social protection systems and service delivery in government-owned nursing homes. This research presents and develops what policy instruments are used in effective nursing home management in East Java. Using qualitative observation and in-depth interviews, this research aims to determine what instruments the Provincial Government uses to manage nursing homes in East Java and what policy instruments can be developed to effectively manage nursing homes in East Java, Indonesia. This research finds that the sort of policy instruments employed by the Government to manage nursing homes effectively encompass family and community, voluntary organization, regulations, information and appeal, and subsidies—next is the development of policy instruments that should be carried out in a public enterprise.